(3QhVGJ GdLfGJ aj CMhGd GdYdeGA hGdSGOGJs - (3GdehShj GdgRGQ LQjHj GdNhGfSGQqj GdCUagGfj, eMeO HGbQ Hf Rjf GdYGHOjf Hf LYaQ (B, 1313 (3g`s
(3ChdgG (B:s
(3GdMeO ddg HGH GdgeRI GdTjN GdLdjd CHh LYaQ CMeO Hf CHj YHO Gddg eMeO Hf NGdO GdHQbj efShH Edi HQbI ef CYeGd be Cbdg chaj bJd LOg GdKGdK eMeO Hf Ydj aj NHjS jhSa Hf YeQ s
(3BNQgG (B:s
(3HGH Gdeje ZjGK GdOjf efUhQ Hf GdSjO GdcHjQ GdCejQ UOQ GdOjf eMeO Hf EHQGgje Hf ESMGb GdMSfj GdMSjfj GdOTJcj GdTjQGRj hcGf JdejP MVQI GdejQ aj GdYdhe GdTQYjI Ydi CHjg hYdi GHf Yeg GdCejQ fXGe GdOjf CMeO GdeJcde Gdabjg aj Gdafhf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\49s
(3EjVGM Gdecfhf (B1\586s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs